2019
DOI: 10.1038/s41598-019-39233-y
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance in the Expression of Genes Associated with Purinergic Signalling in the Lung and Systemic Arteries of COPD Patients

Abstract: Growing evidence indicates that purinergic signalling is involved in the pathogenesis of chronic obstructive pulmonary disease (COPD) and in the vascular remodelling that occurs in other disorders; however, its role in initial vascular changes of COPD is not entirely known. We hypothesised that expression of genes regulating extracellular ATP and adenosine levels would be altered in the lung and systemic arteries of COPD patients. Quantitative real-time PCR was performed to analyse the relative expression of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Cigarette smoking is the most common underlying mechanism of COPD development, and COPD patients are mostly current or former smokers, which was confirmed by our study. Previously, an increase in eATP was observed in BAL of a mouse model of smoke-induced acute lung inflammation and emphysema 12,33 as well as in BAL of COPD patients, even after smoking cessation 9,13 . In this study, control smokers had higher eATP concentrations in plasma from control non-smokers, although the levels were lower than in COPD patients, which might suggest some initial tissue changes ( e.g .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Cigarette smoking is the most common underlying mechanism of COPD development, and COPD patients are mostly current or former smokers, which was confirmed by our study. Previously, an increase in eATP was observed in BAL of a mouse model of smoke-induced acute lung inflammation and emphysema 12,33 as well as in BAL of COPD patients, even after smoking cessation 9,13 . In this study, control smokers had higher eATP concentrations in plasma from control non-smokers, although the levels were lower than in COPD patients, which might suggest some initial tissue changes ( e.g .…”
Section: Discussionmentioning
confidence: 92%
“…demonstrated that expression of P2X7R and P2Y2R were down-regulated in the lungs of non-obstructed smokers and COPD patients, but their study included patients in an early stage of COPD and a very few of them. Moreover, their study population had both lung cancer and COPD, so there might had been a bias regarding the observations associated with COPD 13 . Increased P2X7R expression in the lungs and BAL cells after LPS stimulation was reported 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defects in purine signaling and metabolism have been wellcharacterized in several inflammatory diseases including lung disorders such as asthma [98][99][100][101][102] or chronic obstructive pulmonary disease (COPD), [103][104][105][106][107] graft-versus-host-disease (GVHD), [108][109][110][111] ischemiareperfusion injury, [112][113][114][115][116] gastrointestinal (GI) inflammation or inflammatory bowel disorder (IBD) [117][118][119][120][121][122] multiple sclerosis (MS), [123][124][125][126][127] and myasthenia gravis, 128,129 among others. Inflammatory disorders in the airway are mediated in part by both enhanced levels of adenosine in the bronchoalveolar lavage fluid and by enhanced hyperresponsiveness to adenosine challenge.…”
Section: When Purinergic Signaling Goes Awrymentioning
confidence: 99%